Prevalence, virulence factors, and antibiotic resistance of Staphylococcus aureus in seafood products - Rasool Esmaili Derke; Ebrahim Rahimi; Amir Shakerian; Faham Khamesipour (BMC Infectious Diseases)
Abstract Introduction Seafood contamination by bacteria is a pervasive issue, contributing to foodborne illnesses. This study investigates the prevalence, virulence factors, and antibiotic resistance in Staphylococcus aureus (S. aureus) isolated from various seafood products. Methods A total of 460 samples, including fresh, smoked, salted, and dried fish, as well as oysters, crab, lobster, and shrimp, were collected in Shahrekord, Iran. S. aureus isolation followed ISO standards, with confirmation via PCR for 16S rRNA and nuc genes. Antibiotic susceptibility was determined via Kirby-Bauer disc diffusion, while PCR detected enterotoxin and antibiotic resistance genes. Findings S. aureus was prevalent in all seafood types, with 27.83% positivity. Methicillin-resistant S. aureus (MRSA) was found in most samples, except oysters and crabs. Virulence genes were common, with Sea, Seb, Sed, Sec, and See being the most prevalent. High resistance to penicillin G and ampicillin (70%- 100%) was observed. Resistance varied for other antibiotics, with linezolid showing 100% susceptibility. The mecA gene was present in over 50% of isolates, with blaZ being the most detected resistance gene. Conclusion The study underscores the need for Good Hygiene Practices (GHP) in seafood processing to mitigate S. aureus transmission. While specific comparisons between sample types were limited, the findings emphasize the prevalence of virulence factors and antibiotic resistance in seafood-associated S. aureus, highlighting the importance of vigilant food safety measures.